Development of a 3D geological/hydrogeological model targeted at sustainable management of the urban water cycle in Odense City, Denmark. (2017) - Mielby, Susie; Sandersen, Peter B.E.
Abstract: Many urban areas in Denmark are facing rising groundwater levels due to decreasing groundwater abstraction, greater rainfall and rising sea level due to climate change. Therefore, solutions for handling excess surface water and groundwater in urban areas are needed. To ensure a good background for a continued and sustainable handling of the urban water cycle, special attention has to be paid to the development of geological/hydrogeological models of the subsurface as a basis for management and planning. A 3D geological/hydrogeological modelling tool for handling the urban water cycle within Odense City has been setup in a collaborative effort involving authorities and private stakeholders. With Odense City as a pilot area the developed tools and the gained experience has been made available for other cities facing similar challenges. This paper introduces the Odense Model, presents the major project considerations during the construction, and briefly presents the model results, the developed tools for urban planning/management and the project considerations concerning the continued use and maintenance of the model.